2008
DOI: 10.1111/j.1574-6976.2007.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and pathogenesis ofStaphylococcus aureus: lessons learned from genotyping and comparative genomics

Abstract: Staphylococcus aureus is an opportunistic pathogen and the major causative agent of numerous hospital- and community-acquired infections. Multilocus sequence typing reveals a highly clonal structure for S. aureus. Although infrequently occurring across clonal complexes, homologous recombination still contributed to the evolution of this species over the long term. agr-mediated bacterial interference has divided S. aureus into four groups, which are independent of clonality and provide another view on S. aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
132
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 95 publications
1
132
0
3
Order By: Relevance
“…In addition, they may be eventually capable of breaking interlineage barriers. An important barrier is the SauI type I restriction-modification system, which appears to be one of the major mechanisms underlying the clonal structure of S. aureus (11,59). Nevertheless, a mobile genetic element can enter a CC from which it was originally excluded by means of a SauI restriction mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they may be eventually capable of breaking interlineage barriers. An important barrier is the SauI type I restriction-modification system, which appears to be one of the major mechanisms underlying the clonal structure of S. aureus (11,59). Nevertheless, a mobile genetic element can enter a CC from which it was originally excluded by means of a SauI restriction mutant.…”
Section: Discussionmentioning
confidence: 99%
“…As in the present study, a strong correlation between ST125 and spa type t067 was observed in both countries. Most of the remaining MRSA (12) CC5 (9), CC15, CC45 lukED (12), lukPV (2) tst (3), sea (7), seb (4), sec (10) eta (6), etb (11), etd (3) sed (12), sej (12), ser (10) (16) agrIII (16) CC5 (4), CC30 (11) lukED (16), lukPV (7) tst (15), sea (15), seb, sec (14) eta (6), etb (15) sed, sej seh (4) egc (4), egc-like (12) V2c (34) agrII ( isolates from the HUCA were also positive for SCCmec IV but belonged to other STs (i.e., ST5, ST228, or ST47); two carried SCCmec I and were of ST228, while one was not typeable by the applied method (60). The ST5-SCCmec IV (pediatric clone) (49) and ST228-SCCmec I (southern German clone) (48) clones are major hospital-acquired MRSA clones, widely distributed worldwide (7,46,56).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, methicillin-resistant Staphylococcus aureus (MRSA) is responsible for approximately 43% of these infections (Sader et al, 2004). Coagulase-negative staphylococci (CNS) is also recognized as a important nosocomial pathogen around the world, highlighting the multiresistant Staphylococcus epidermidis and Staphylococcus haemolyticus as the most isolated organisms from bacteremia (Nunes et al, 2007) and infections related to implanted medical devices (Uçkay et al, 2009) Resistance to methicillin is relevant in these pathogens because is related to resistance to other β-lactams and can be associated with resistance to other classes of antimicrobials (Feng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…al., 2012). Comparative genomics helps to improve knowledge on pathogenesis and drug resistance of microbial species (Feng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%